Who owns the forest? extractive capitalism, indigenous sovereignty, and narrative resistance in Indonesian environmental literature - Dani Setiaji (Indonesian Journal of Politics and Literary Studies, 2026)
Background: Forest conflicts in Indonesia reveal that ownership is not only a legal question but also a struggle over memory, livelihood, ecological authority, and narrative legitimacy. Objective: This study aims to examine how Indonesian environmental literature represents extractive capitalism, Indigenous sovereignty, and narrative resistance in forest-centered narratives. Method: Using qualitative literary analysis, this study analyzes seven publicly verifiable Indonesian literary texts through political-ecological coding, eco-postcolonial close reading, Indigenous sovereignty analysis, and a narrative-resistance grid. Results: Findings show that forest ownership is represented as a contested field where concessionary access, timber labour, ecological depletion, and customary restraint produce competing claims over land and authority. Findings also indicate that Indigenous sovereignty appears through relational forms, including ritual memory, ecological knowledge, sacred trees, mythic agency, livelihood attachment, and more-than-human obligation. Implication: Findings further demonstrate that resistance operates through narrative form, especially testimony, labour witnessing, ecological warning, atmospheric symbolism, curse, mythic refusal, and sacred metaphor. Novelty: This study offers novelty by integrating extractive capitalism, Indigenous sovereignty, and narrative resistance into one eco-postcolonial framework for reading Indonesian environmental literature as a counter-archive of forest injustice.